Alumina ceramic slurry, alumina ceramic, preparation method and application of alumina ceramic, and gas sensor

By adding specific content of binder and sintering aid to the alumina ceramic slurry, the sintering temperature and shrinkage rate are adjusted to match it with YSZ ceramics, the warping and layering problems of traditional alumina ceramics when sintering on YSZ ceramics are solved, and the flatness and performance of the gas sensor are improved.

CN119569429APending Publication Date: 2025-03-07CHINA FAW CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411793469.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

Traditional alumina ceramics are prone to warping and delamination when sintered on YSZ ceramics, affecting the flatness and performance of the gas sensor.

Method used

By adding a specific content of the composite component binder and sintering aid to the alumina ceramic slurry, the viscosity and sintering temperature of the alumina ceramic are adjusted so that its sintering temperature is close to that of the YSZ ceramic and the shrinkage rate is close to that of the sintering temperature.

Benefits of technology

It effectively improves the warping and layering problems of the ceramic layer during sintering, and improves the flatness and device performance of the gas sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides aluminum oxide ceramic slurry, aluminum oxide ceramic, a preparation method and application of the aluminum oxide ceramic and a gas sensor. Wherein the aluminum oxide ceramic slurry comprises the following components in percentage by mass: 5%-9% of an organic solvent, 2%-4% of a plasticizer, 0.6%-2.2% of a binder, 60%-80% of aluminum oxide powder and 10%-30% of a sintering aid; wherein the binder comprises the following components in percentage by mass: 2%-5% of polyethylene glycol-4000, 5%-10% of polyvinyl alcohol and 85%-93% of water; the sintering aid comprises silicon dioxide and boron oxide. According to the alumina ceramic slurry disclosed by the invention, the problems of warping of a ceramic layer and layering between Al2O3 ceramic and YSZ ceramic in a sintering process can be improved, and the flatness and device performance of a gas sensor can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of gas sensors, and in particular to an alumina ceramic slurry, an alumina ceramic, a preparation method and application thereof, and a gas sensor. Background Art

[0002] Oxygen sensors are widely used in modern automobile electronic fuel injection engine control systems to detect the oxygen concentration in the engine exhaust and feed the output signal back to the computer, thereby controlling the amount of fuel injection and enabling the three-way catalytic converter to ensure the best air purification rate. The key role of the oxygen sensor is played by the multilayer ceramic sensor element, which mainly includes a solid electrolyte, a reaction electrode, and a reference electrode.

[0003] Y2O3 stabilized ZrO2 (YSZ) ceramics are often used as solid electrolyte layers for oxygen sensors because of their high oxygen ion conductivity, strong stability, high strength, and corrosion resistance. YSZ ceramics have a high resistivity below 350°C and cannot work properly. They need to be heated by heating electrodes at the moment of engine start. However, the heated electrodes will be in direct contact with the solid electrolyte, which will interfere with the voltage signal generated by the solid electrolyte, so an insulating layer must be added between the two to play an insulating role.

[0004] The insulating layer often uses Al2O3 ceramics with good high-temperature insulation properties. However, when using Al2O3 ceramics as the insulating layer, warping is prone to occur during the sintering process, affecting the flatness of the sensor. Also, delamination is prone to occur between Al2O3 ceramics and YSZ ceramics during the sintering process, affecting the performance of the sensor.

[0005] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0006] Based on this, the present application provides an alumina ceramic slurry to alleviate the problem of warping and delamination of alumina ceramics when sintering to prepare alumina ceramic layers on YSZ ceramics, and correspondingly provides an alumina ceramic and its preparation method and application, and a gas sensor.

[0007] The technical solution proposed in this application is as follows:

[0008] According to a first aspect of the present application, an alumina ceramic slurry is provided, wherein the alumina ceramic slurry comprises the following components by mass fraction:

[0009] Organic solvent 5%~9%, plasticizer 2%~4%, binder 0.6%~2.2%, alumina powder 60%~80% and sintering aid 10%~30%;

[0010] The binder comprises the following components by mass fraction: 2% to 5% polyethylene glycol-4000, 5% to 10% polyvinyl alcohol, and 85% to 93% water; the sintering aid comprises silicon dioxide and boron oxide.

[0011] In any embodiment, the mass fraction of the silicon dioxide in the sintering aid is 84% ​​to 94%, and the mass fraction of the boron oxide is 6% to 16%.

[0012] In any embodiment, the organic solvent includes one or more of terpineol, ethanol and xylene.

[0013] In any embodiment, the plasticizer includes one or more of dibutyl phthalate, ethyl cellulose, and butyl benzyl phthalate.

[0014] In any embodiment, the weight average molecular weight of the polyvinyl alcohol is 25,000 to 35,000.

[0015] According to a second aspect of the present application, a method for preparing an alumina ceramic is provided, comprising the following steps:

[0016] Providing the alumina ceramic slurry of the first aspect of the present application;

[0017] The alumina ceramic slurry is dried and first sintered in sequence to obtain the alumina ceramic.

[0018] In any embodiment, the temperature of the first sintering is 1400° C. to 1500° C., and the time of the first sintering is 60 h to 80 h.

[0019] According to a third aspect of the present application, an alumina ceramic is provided. The alumina ceramic is prepared by the preparation method of the alumina ceramic according to the second aspect of the present application.

[0020] According to a fourth aspect of the present application, there is provided an application of the alumina ceramic according to the third aspect of the present application in a gas sensor.

[0021] In any embodiment, the alumina ceramic is provided as an insulating layer on the Y2O3-stabilized ZrO2 ceramic in the gas sensor.

[0022] According to a fifth aspect of the present application, a gas sensor is provided, comprising the alumina ceramic according to the third aspect of the present application.

[0023] In any embodiment, the gas sensor comprises Y2O3-stabilized ZrO2 ceramic, and the alumina ceramic is disposed on the Y2O3-stabilized ZrO2 ceramic.

[0024] In any embodiment, the gas sensor is an oxygen sensor or a nitrogen oxide sensor.

[0025] According to a sixth aspect of the present application, a method for preparing a gas sensor is provided, comprising the following steps:

[0026] Provide Y2O3 stabilized ZrO2 ceramic green sheets;

[0027] Coating the alumina ceramic slurry of the first aspect of the present application on the Y2O3-stabilized ZrO2 ceramic green sheet to obtain a Y2O3-stabilized ZrO2 ceramic green sheet having a ceramic slurry layer;

[0028] The Y2O3-stabilized ZrO2 ceramic green sheet having the ceramic slurry layer is subjected to a second sintering.

[0029] In any embodiment, the temperature of the second sintering is 1400° C. to 1500° C., and the time of the second sintering is 60 h to 80 h.

[0030] Compared with the traditional technology, this application has at least the following beneficial effects:

[0031] By adding a binder with a specific content of composite components to the alumina ceramic slurry and adding a sintering aid with a specific content and type, the viscosity and sintering temperature of the alumina ceramic slurry can be effectively regulated, and the film thickness and shrinkage of the alumina ceramic can be regulated, so that the sintering temperature of the alumina ceramic is close to the sintering temperature of the YSZ ceramic, and the shrinkage of the alumina ceramic and the YSZ ceramic are close at the sintering temperature; thereby, the problems of warping of the ceramic layer and delamination between the Al2O3 ceramic and the YSZ ceramic during the sintering process can be improved, and the flatness and device performance of the gas sensor can be improved. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.

[0034] Some embodiments of the present application provide an alumina ceramic slurry, which includes the following components by mass fraction: 5%~9% organic solvent, 2%~4% plasticizer, 0.6%~2.2% binder, 60%~80% alumina powder and 10%~30% sintering aid; wherein the binder includes the following components by mass fraction: 2%~5% polyethylene glycol-4000, 5%~10% polyvinyl alcohol, 85%~93% water; the sintering aid includes silica and boron oxide.

[0035] Y2O3 stabilized ZrO2 (YSZ) ceramics are often used as solid electrolyte layers in gas sensors (such as oxygen sensors). YSZ ceramics need to be heated by heating electrodes at the moment of engine start-up to make the YSZ ceramics have a lower resistance. However, the heated electrodes will directly contact the YSZ ceramics, which will interfere with the voltage signal generated by the YSZ ceramics. In this regard, an Al2O3 ceramic layer is usually added to the YSZ ceramics as an insulating layer to avoid direct contact between the electrodes and the YSZ ceramics.

[0036] In traditional technology, Al2O3 ceramic slurry is usually coated on YSZ ceramics, and then the Al2O3 ceramic layer is prepared as an insulating layer by sintering. However, since the sintering temperature of YSZ ceramics does not match the sintering temperature of Al2O3 ceramics, the sintering temperature of Al2O3 ceramics is higher than that of YSZ ceramics, and the shrinkage rates of alumina and zirconia during sintering are different, the ceramic layer is prone to warping during the sintering process, affecting the flatness of the gas sensor; and during the sintering process, stratification is prone to occur between Al2O3 ceramics and YSZ ceramics, affecting the performance of the gas sensor.

[0037] In this regard, the present application adds a binder with a specific content of composite components to the alumina ceramic slurry, and adds a sintering aid with a specific content and type, so as to effectively control the viscosity and sintering temperature of the alumina ceramic slurry, and control the film thickness and shrinkage of the alumina ceramic, so that the sintering temperature of the alumina ceramic is close to that of the YSZ ceramic, and the shrinkage of the alumina ceramic is close to that of the YSZ ceramic at the sintering temperature; thereby improving the warping of the ceramic layer during the sintering process and the stratification between the Al2O3 ceramic and the YSZ ceramic, and improving the flatness and device performance of the gas sensor. In addition, the binder with the above-mentioned composite components is conducive to improving the bonding force between the Al2O3 ceramic and the YSZ ceramic, and improving the overall strength of the solid electrolyte.

[0038] The shrinkage rate refers to the linear shrinkage rate of the green ceramic sheet before and after sintering, which is the ratio of the dimensional change in the length direction of the green ceramic sheet before and after sintering to the original size. The linear shrinkage rate is expressed as a percentage (%).

[0039] It can be understood that the mass fraction of the organic solvent in the alumina ceramic slurry can be 5%, 6%, 7%, 8%, 9% and any value within the range formed by any two of the above values; the mass fraction of the plasticizer can be 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4% and any value within the range formed by any two of the above values; the mass fraction of the binder can be 0.6%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2% and any value within the range formed by any two of the above values; the mass fraction of the alumina powder can be 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80% and any value within the range formed by any two of the above values; the mass fraction of the sintering aid can be 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30% and any value within the range formed by any two of the above values. The mass fraction of polyethylene glycol in the binder can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% and any value within the range formed by any two of the above values; the mass fraction of polyvinyl alcohol can be 5%, 6%, 7%, 8%, 9%, 10% and any value within the range formed by any two of the above values; the mass fraction of water can be 85%, 88%, 90%, 92%, 93% and any value within the range formed by any two of the above values.

[0040] In some of the embodiments, the mass fraction of silicon dioxide in the sintering aid is 84% ​​to 94%, and the mass fraction of boron oxide is 6% to 16%. The silicon dioxide and boron oxide in the sintering aid are glass materials. Adding the above-mentioned silicon dioxide and boron oxide as sintering aids to the alumina ceramic slurry can effectively reduce the sintering temperature and shrinkage of the alumina ceramic, making the sintering temperature and shrinkage of the alumina ceramic consistent with those of the YSZ ceramic, further improving the warping of the ceramic layer during the sintering process and the delamination between the Al2O3 ceramic and the YSZ ceramic, and further improving the flatness and device performance of the gas sensor.

[0041] It can be understood that the mass fraction of silicon dioxide in the sintering aid can be 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% and any value within the range formed by any two of the above values; the mass fraction of boron oxide can be 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16% and any value within the range formed by any two of the above values.

[0042] In some embodiments, the organic solvent includes one or more of pinene alcohol, ethanol and xylene. The above organic solvent can effectively disperse the alumina powder particles, so that the alumina powder forms a uniform and stable slurry system, avoids the agglomeration of the alumina powder particles, and thus makes the prepared alumina ceramic layer have good quality. In addition, the above organic solvent can effectively dissolve the binder, so that it forms a uniform bonding layer on the surface of the alumina powder particles, which is beneficial to improve the bonding force between the alumina ceramic particles and improve the overall strength of the ceramic layer.

[0043] In some embodiments, the plasticizer includes one or more of dibutyl phthalate, ethyl cellulose and butyl benzyl phthalate. By adding the above plasticizer to the alumina ceramic slurry, it is beneficial to reduce the viscosity of the alumina ceramic slurry and improve the fluidity of the slurry. By combining the plasticizer with the binder, the alumina ceramic slurry can have a suitable viscosity, and the film-forming performance and shrinkage rate of the alumina ceramic slurry can be regulated.

[0044] In some embodiments, the weight average molecular weight of polyvinyl alcohol is 25,000 to 35,000, and the D90 particle size of the alumina powder is 1 μm to 2 μm, and can be 1 μm. The D90 particle size refers to the particle size value corresponding to 90% of the cumulative distribution percentage from small to large in the particle size distribution.

[0045] One embodiment of the present application provides a method for preparing an alumina ceramic, the preparation method comprising the following steps: first providing the alumina ceramic slurry mentioned above in the present application; sequentially drying and performing a first sintering on the alumina ceramic slurry to obtain an alumina ceramic.

[0046] In some specific examples, the organic solvent, plasticizer and binder are first weighed according to the mass fraction and placed in a beaker, and the materials are mixed evenly by magnetic stirring to obtain an organic carrier; then the alumina powder and the sintering aid are weighed according to the mass fraction, and the organic carrier, alumina powder and the sintering aid are placed in a ball mill for ball milling; after mixing evenly, the slurry is centrifugally stirred and vacuum degassed; then the slurry is sealed and refrigerated; the slurry is cast and dried to obtain a green porcelain tape, which is sintered after warm isostatic pressing to form an alumina ceramic sheet.

[0047] In other specific examples, the organic solvent, plasticizer and binder are first weighed according to the mass fraction and placed in a beaker, and the materials are mixed evenly by magnetic stirring to obtain an organic carrier; then the alumina powder and the sintering aid are weighed according to the mass fraction, and the organic carrier, alumina powder and the sintering aid are placed in a ball mill for ball milling; after mixing evenly, the slurry is centrifugally stirred and vacuum degassed; then the slurry is sealed and refrigerated; the slurry is screen-printed on a YSZ ceramic green sheet, and sintered after warm isostatic pressing, thereby obtaining a laminated structure in which an alumina ceramic layer is composited on a YSZ ceramic layer.

[0048] In any embodiment, the temperature of the first sintering is 1400°C to 1500°C, and the time of the first sintering is 60h to 80h. In some specific examples, the temperature of the first sintering is 1450°C. The method for preparing the alumina ceramic of the present application, by using the alumina ceramic slurry of the present application, has a sintering temperature close to the sintering temperature of the YSZ ceramic green sheet, and the shrinkage rate of the alumina ceramic at the sintering temperature is close to the shrinkage rate of the YSZ ceramic green sheet.

[0049] In one embodiment of the present application, an alumina ceramic is provided, and the alumina ceramic is prepared by the alumina ceramic preparation method described above. It is understood that the alumina ceramic can be an alumina ceramic sheet obtained by tape-casting, drying, and sintering an alumina ceramic slurry; or it can be a laminated structure having an alumina ceramic layer obtained by coating an alumina ceramic slurry on a YSZ ceramic green sheet or other substrate and sintering the alumina ceramic slurry.

[0050] The alumina ceramic of the present application is prepared by sintering the alumina ceramic slurry of the present application, and has a sintering temperature and shrinkage rate close to those of the YSZ ceramic green sheet. The YSZ ceramic laminated structure with the alumina ceramic layer formed has good quality of the laminated structure, and the ceramic layer is not prone to warping and delamination. When the laminated structure is applied to a gas sensor, it is beneficial to improve the flatness and device performance of the gas sensor.

[0051] In one embodiment of the present application, an application of the above-mentioned alumina ceramic of the present application in a gas sensor is provided. Specifically, the alumina ceramic is provided as an insulating layer on the YSZ ceramic in the gas sensor to form a laminated structure in which the alumina ceramic layer is composited on the YSZ ceramic layer. The laminated structure can be used as a solid electrolyte layer of the gas sensor, wherein the alumina ceramic layer as an insulating layer can prevent the electrode from directly contacting the YSZ ceramic layer during heating.

[0052] By using the alumina ceramic of the present application as an insulating layer on the YSZ ceramic in a gas sensor, the problem of warping and delamination of the alumina ceramic insulating layer on the YSZ ceramic in the traditional technology can be effectively solved, thereby improving the flatness and device performance of the gas sensor.

[0053] In some specific examples, the gas sensor may be an oxygen sensor or a nitrogen oxide sensor. The oxygen sensor or the nitrogen oxide sensor may be applied to an automotive electronic fuel injection engine control system to detect the concentration of oxygen and nitrogen oxides in the engine exhaust and feed the output signal back to the computer to control the amount of fuel injection.

[0054] In one embodiment of the present application, a gas sensor is also provided, which includes the alumina ceramic described above in the present application. Specifically, the gas sensor includes YSZ ceramics, and the alumina ceramics are arranged on the YSZ ceramics. The gas sensor may be an oxygen sensor or a nitrogen oxide sensor. By providing the alumina ceramic described above in the present application as an insulating layer on the YSZ ceramic of the gas sensor, direct contact between the electrode and the YSZ ceramic layer during heating can be effectively avoided, and the problems of warping and delamination of the alumina ceramic insulating layer can be alleviated, thereby improving the flatness and device performance of the gas sensor.

[0055] One embodiment of the present application also provides a method for preparing the above-mentioned gas sensor, and the preparation method includes the following steps: first, providing a YSZ ceramic green sheet; then coating the above-mentioned alumina ceramic slurry of the present application on the YSZ ceramic green sheet to obtain a YSZ ceramic green sheet with an alumina ceramic slurry layer; performing a second sintering on the above-mentioned YSZ ceramic green sheet with the alumina ceramic slurry layer to obtain a solid electrolyte for the gas sensor; combining the above-mentioned solid electrolyte with a reaction electrode and a reference electrode into a ceramic sensor element, and then encapsulating the ceramic sensor element to form a gas sensor.

[0056] The preparation method of the above-mentioned gas sensor is as follows: by coating the alumina ceramic slurry of the present application on a YSZ ceramic green sheet, the YSZ ceramic green sheet with the alumina ceramic slurry layer is subjected to a second sintering to form a laminated structure having an alumina ceramic layer as an insulating layer on the YSZ ceramic layer; the laminated structure is used as a solid electrolyte to form a ceramic sensing element with a reaction electrode and a reference electrode, and then packaged to form a gas sensor; the problem of warping and delamination of the alumina ceramic insulating layer can be effectively alleviated, and the flatness and device performance of the gas sensor can be improved.

[0057] In any embodiment, the temperature of the second sintering is 1400°C to 1500°C, and the time of the second sintering is 60h to 80h. In some specific examples, the temperature of the second sintering is 1450°C. The sintering temperature of the alumina ceramic slurry of the present application is close to the sintering temperature of the YSZ ceramic green sheet, and the shrinkage rate of the alumina ceramic at the sintering temperature is close to the shrinkage rate of the YSZ ceramic green sheet. It is helpful to alleviate the problem of warping and delamination of the alumina ceramic insulating layer during the sintering process.

[0058] The present application will be further described below in conjunction with specific embodiments and comparative examples, but they should not be construed as limiting the scope of protection of the present application.

[0059] Embodiment 1:

[0060] (1) Weigh 100 g of an organic solvent, 40 g of a plasticizer, and 10 g of a binder (including 5 wt % of polyethylene glycol-4000, 8 wt % of polyvinyl alcohol with a weight average molecular weight of 30,000, and 87 wt % of water), place them in a beaker, and mix them evenly by magnetic stirring at a speed of 200 r / min to prepare an organic carrier;

[0061] (2) Weigh 1000 g of alumina powder, place 150 g of the above-mentioned organic carrier, 1000 g of alumina powder, and 200 g of sintering aid (including 90 wt % of silicon dioxide and 10 wt % of boron oxide) in a ball mill for ball milling for 2 h at a ball milling speed of 70 r / min;

[0062] (3) After being evenly mixed, the slurry is centrifuged and vacuum degassed at a centrifugal stirring speed of 200 r / min and a negative pressure of 1 MPa for vacuum degassed;

[0063] (4) The slurry is sealed and refrigerated at 5.8°C;

[0064] (5) The slurry is cast and dried to obtain a green ceramic tape, which is then isostatically pressed and sintered at 1450°C for 72 hours to obtain an alumina ceramic sheet. The shrinkage of the alumina ceramic sheet is 23.4%.

[0065] Embodiment 2:

[0066] (1) Weigh 100 g of an organic solvent, 40 g of a plasticizer, and 30 g of a binder (including 5 wt % of polyethylene glycol-4000, 10 wt % of polyvinyl alcohol with a weight average molecular weight of 30,000, and 85 wt % of water), place them in a beaker, and mix them evenly by magnetic stirring at a speed of 200 r / min to prepare an organic carrier;

[0067] (2) Weigh 1000 g of alumina powder, place 170 g of the above-mentioned organic carrier, 1000 g of alumina powder, and 200 g of sintering aid (including 84 wt % of silicon dioxide and 16 wt % of boron oxide) in a ball mill for ball milling for 2 h at a ball milling speed of 70 r / min;

[0068] (3) After being evenly mixed, the slurry is subjected to centrifugal stirring and vacuum degassing, the centrifugal stirring speed is 200 r / min, and the negative pressure of vacuum degassing is 1 MPa;

[0069] (4) The slurry is sealed and refrigerated at 5.8°C;

[0070] (5) The slurry was screen-printed on a YSZ ceramic green sheet, and then sintered at 1450°C after warm isostatic pressing to obtain a laminated structure with an alumina ceramic layer on the YSZ ceramic. The shrinkage of the alumina ceramic sheet was 22.5%, and the shrinkage of the YSZ ceramic sheet was 22.4%.

[0071] (6) The above-mentioned stacked structure is used as a solid electrolyte, combined with a reaction electrode and a reference electrode to form a ceramic sensor element, and then the ceramic sensor element is packaged to form an oxygen sensor.

[0072] Embodiment 3:

[0073] (1) Weigh 100 g of an organic solvent, 40 g of a plasticizer, and 30 g of a binder (including 5 wt% of polyethylene glycol-4000, 5 wt% of polyvinyl alcohol with a weight average molecular weight of 30,000, and 90 wt% of water), place them in a beaker, and mix them evenly by magnetic stirring at a speed of 200 r / min to prepare an organic carrier;

[0074] (2) Weigh 1000 g of alumina powder, place 170 g of the above-mentioned organic carrier, 1000 g of alumina powder, and 200 g of sintering aid (including 94 wt % of silicon dioxide and 6 wt % of boron oxide) in a ball mill for ball milling for 2 h at a ball milling speed of 70 r / min;

[0075] (3) After being evenly mixed, the slurry is subjected to centrifugal stirring and vacuum degassing, the centrifugal stirring speed is 200 r / min, and the negative pressure of vacuum degassing is 1 MPa;

[0076] (4) The slurry is sealed and refrigerated at 5.8°C;

[0077] (5) The slurry was screen-printed on a YSZ ceramic green sheet, and then sintered at 1450°C after warm isostatic pressing to obtain a laminated structure with an alumina ceramic layer on the YSZ ceramic. The shrinkage of the alumina ceramic sheet was 20.2%, and the shrinkage of the YSZ ceramic sheet was 20.4%.

[0078] (6) The above-mentioned stacked structure is used as a solid electrolyte, combined with a reaction electrode and a reference electrode to form a ceramic sensor element, and then the ceramic sensor element is packaged to form an oxygen sensor.

[0079] Comparative Example 1:

[0080] Comparative Example 1 is substantially the same as Example 2, except that no sintering aid is added in step (2).

[0081] Comparative Example 2:

[0082] Comparative Example 2 is basically the same as Example 2, except that the binder in step (1) is polyvinyl alcohol.

[0083] Test method:

[0084] (1) Shrinkage test

[0085] Use a vernier caliper or micrometer to test the length dimension of the green ceramic sheet before and after sintering, and calculate the ratio of the size change of the green ceramic sheet in the length direction before and after sintering to the original size, which is the shrinkage rate of the green ceramic sheet before and after sintering.

[0086] The specific steps are as follows: Before sintering the green ceramic sheet, accurately measure its length and record it as the initial size L0; after sintering, cool it to room temperature and measure the corresponding size of the ceramic layer again and record it as the final size L1. The linear shrinkage rate is obtained by calculating the ratio of the size change to the initial size. Shrinkage rate = (L0-L1) / L0×100%.

[0087] (2) Layered testing

[0088] The ceramic layer is sliced, and then the cross section of the slice is observed under a microscope to observe the bonding between the alumina ceramic and the YSZ ceramic layer, and whether there is delamination.

[0089] The shrinkage rate of the alumina ceramic layer and the YSZ ceramic layer, the flatness and the delamination of the alumina ceramic layer in the above embodiments and comparative examples were tested.

[0090] The test results are shown in Table 1. In Table 1, “ / ” means not tested.

[0091] Table 1

[0092]

[0093] It can be seen from Table 1 that the shrinkage rate of the alumina ceramic layer of the embodiment of the present application before and after sintering is close to the shrinkage rate of the YSZ ceramic layer before and after sintering, and no obvious warping and delamination phenomena occur.

[0094] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0095] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An alumina ceramic slurry, characterized in that: The following components are included by mass fraction: Organic solvent 5%~9%, plasticizer 2%~4%, binder 0.6%~2.2%, alumina powder 60%~80% and sintering aid 10%~30%; The binder comprises the following components by mass fraction: 2% to 5% polyethylene glycol-4000, 5% to 10% polyvinyl alcohol, and 85% to 93% water; the sintering aid comprises silicon dioxide and boron oxide.

2. The alumina ceramic slurry according to claim 1, characterized in that: The mass fraction of the silicon dioxide in the sintering aid is 84% ​​to 94%, and the mass fraction of the boron oxide is 6% to 16%.

3. The alumina ceramic slurry according to claim 1 or 2, characterized in that: The organic solvent includes one or more of terpineol, ethanol and xylene; And / or, the plasticizer includes one or more of dibutyl phthalate, ethyl cellulose and butyl benzyl phthalate.

4. The alumina ceramic slurry according to claim 1 or 2, characterized in that: The weight average molecular weight of the polyvinyl alcohol is 25,000 to 35,000.

5. A method for preparing alumina ceramics, characterized in that: The following steps are involved: Providing an alumina ceramic slurry according to any one of claims 1 to 4; The alumina ceramic slurry is dried and first sintered in sequence to obtain the alumina ceramic.

6. The method for preparing alumina ceramics according to claim 5, characterized in that: The temperature of the first sintering is 1400° C. to 1500° C., and the time of the first sintering is 60 h to 80 h.

7. An alumina ceramic, characterized in that: The alumina ceramic is prepared by the method for preparing the alumina ceramic according to claim 5 or 6.

8. Use of the alumina ceramics according to claim 7 in a gas sensor.

9. The use according to claim 8, characterized in that: The alumina ceramic is used as an insulating layer and is disposed on the Y2O3-stabilized ZrO2 ceramic in the gas sensor.

10. A gas sensor, characterized in that: Comprising the alumina ceramics as described in claim 7.

11. The gas sensor according to claim 10, characterized in that: The gas sensor comprises Y2O3-stabilized ZrO2 ceramics, and the alumina ceramics are arranged on the Y2O3-stabilized ZrO2 ceramics.

12. The gas sensor according to claim 10 or 11, characterized in that: The gas sensor is an oxygen sensor or a nitrogen oxide sensor.

13. A method for preparing a gas sensor, characterized in that: The following steps are involved: Provide Y2O3 stabilized ZrO2 ceramic green sheets; Coating the alumina ceramic slurry according to any one of claims 1 to 4 on the Y2O3-stabilized ZrO2 ceramic green sheet to obtain a Y2O3-stabilized ZrO2 ceramic green sheet having a ceramic slurry layer; The Y2O3-stabilized ZrO2 ceramic green sheet having the ceramic slurry layer is subjected to a second sintering.

14. The method for preparing a gas sensor according to claim 13, characterized in that: The temperature of the second sintering is 1400° C. to 1500° C., and the time of the second sintering is 60 h to 80 h.